RESEARCH OF COMPETITION IN THE FUNCTION OF POSITIONING THE ORGANIZATION IN THE BUSINESS MARKET - Jovičić, Dragoljub; Stankov, Biljana; Vranješ, Marija (International Journal of Economic Practice and Policy, 2015)
All marketers tend to position their company and its products and/or services in the market the best they could. In this context, they must develop and implement in practice a complete marketing strategy, which is undoubtedly based on three concepts: segmentation, targeting and positioning. If marketers want to successfully separate the image of their company and its brand in the minds of potential customers and users in business market it is necessary to obtain and analyze a sufficient number of accurate and relevant information from the environment. Although pieces of information about customers, suppliers and other participants in the marketing channel are significant, latterly information about competition are more important. Without a thorough and continuous research and monitoring of competition, marketers could not provide management of the company with relevant information about competing organizations, which would result in an absolutely negative impact on the quality of future management decisions. In this context, the subject of this paper is theoretical analysis of competition, and the aim of the research is to assess the real attitudes of managers in the Serbian market of styrofoam and styrodur, about the most relevant characteristics of the competition – which have a strong impact on organization’s operations.